2018
DOI: 10.3389/fphy.2018.00122
|View full text |Cite
|
Sign up to set email alerts
|

Non-symmetrized Hyperspherical Harmonics Method for Non-equal Mass Three-Body Systems

Abstract: The non-symmetrized hyperspherical harmonics method for a three-body system, composed by two particles having equal masses, but different from the mass of the third particle, is reviewed and applied to the 3 H, 3 He nuclei and 3 Λ H hyper-nucleus, seen respectively as nnp, ppn and N N Λ three-body systems. The convergence of the method is first tested in order to estimate its accuracy. Then, the difference of binding energy between 3 H and 3 He due to the difference of the proton and the neutron masses is stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
4
5
0
Order By: Relevance
“…Using this relation, it is found that B Λ ( 3 Λ H) = 0.237 MeV. The convergence behaviour shown in these results is identical to that in [49], where the Non-Symmetrized Hyperspherical Harmonics method was used in computing the binding energy of a triton. Using lambda-nucleon Gaussian potentials from [50], the computed hypertriton binding energy in [49] also showed a comparable convergence behaviour.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Using this relation, it is found that B Λ ( 3 Λ H) = 0.237 MeV. The convergence behaviour shown in these results is identical to that in [49], where the Non-Symmetrized Hyperspherical Harmonics method was used in computing the binding energy of a triton. Using lambda-nucleon Gaussian potentials from [50], the computed hypertriton binding energy in [49] also showed a comparable convergence behaviour.…”
Section: Resultssupporting
confidence: 64%
“…The convergence behaviour shown in these results is identical to that in [49], where the Non-Symmetrized Hyperspherical Harmonics method was used in computing the binding energy of a triton. Using lambda-nucleon Gaussian potentials from [50], the computed hypertriton binding energy in [49] also showed a comparable convergence behaviour. In some applications of the hyperspherical harmonics method, convergence is usually accelerated by including either a pair correlation factor or a Jastrow correlation factor in Equation (17).…”
Section: Resultssupporting
confidence: 63%
“…[5] for the mass difference effect for 3 H is 2 keV, and for 3 He is 7 keV calculated using a semi-realistic potential. Similar calculations [7] performed with different N N potentials resulted in the differences from 4 keV to 7 keV for the 3 H. Comparing both models, AAA and AAB, we assume that the mass difference adds uncertainty of several keV to AAA calculations for the 3 H binding energy when a comparison with experimental data is proposed. This uncertainty is above the numerical accuracy of ≤ 1 keV evaluated for the realistic AAA calculations in Refs.…”
Section: Introductionmentioning
confidence: 79%
“…Different applications followed this procedure for bosons as well as for fermions (see Refs. [31,[50][51][52][53]). The advantage of eliminating the orthonormalization of the states has to be balanced by the fact that in this case one has to work with the full basis of HH functions, whose degenerancy rapidly increases with K and the number of particles A.…”
Section: [K]mentioning
confidence: 99%
“…( 48) the first order results of Eqs. ( 50) and (53). Such second-order calculation provides then a symmetric Kmatrix.…”
Section: The a = 3 And 4 Scattering Statesmentioning
confidence: 99%